1522. Safety and Efficacy of CR6261 in an Influenza A H1N1 Healthy Human Challenge Model. (31st December 2020) - Han, Alison; Czajkowski, Lindsay; Rosas, Luz Angela; Cervantes-Medina, Adriana; Xiao, Yongli; Gouzoulis, Monica; Lumbard, Keith; Hunsberger, Sally; Reed, Susan; Athota, Rani; Baus, Holly; Lwin, Amy; et al.
Abstract: Background: Influenza virus infections cause significant morbidity and mortality during yearly seasonal epidemics and during sporadic pandemics. It is imperative to identify new targets for vaccines and therapeutics. One such target is the relatively conserved stalk region of the influenza A hemagglutinin (HA) surface protein. Methods: We conducted a randomized, double-blind, Phase II placebo-controlled trial of a monoclonal antibody that targets the HA stalk (CR6261) in a H1N1pdm09 healthy volunteer human challenge model. CR6261 was infused 24 hours after challenge with H1N1pdm09 and the primary efficacy outcome was area under the curve (AUC) of viral shedding. Results: Between March 2015-May 2018, 104 healthy volunteers were enrolled and randomized with 91 undergoing influenza challenge, of which 49 participants (54%) received treatment with CR6261 and 42 participants (46%) received placebo. A mean of 1x10 6 ng/mL of serum CR6261 was detected by 24 hours after infusion. Nasal CR6261 levels reached a peak mean of 5.97x10 2 ng/ml 2 days after infusion. There was no statistically significant difference in the primary outcome measure between the CR6261 group and placebo (median AUC 48.56 and 25.53 respectively, P=0.31). The severity of illness was compared between the two groups, and no significant difference was observed in number of symptoms, duration of symptoms, or FLU-PRO scores. Conclusion: CR6261 had no statistically significant effect on AUC of viral shedding, and no clinically significant effect on overall influenza disease. Preexisting anti-neuraminidase (NA) antibody titers were most predictive of reduced influenza disease. Nasal CR6261 levels were much lower compared to serum, which may be a factor in the limited effect of CR6261 on this upper respiratory infection. These results suggest that a monoclonal anti-stalk approach to prevent or treat influenza infection may have limited efficacy. Future approaches should consider including and evaluating anti-stalk antibodies as part of a multi-faceted strategy rather than as a standalone therapeutic or vaccine strategy. Funding: This study was funded in part by the intramural program of NIAID, NIH, by the NCI Contract No. 75N910D00024, Task Order No. 75N91019F00130, and through a CRADA with Janssen Infectious Diseases and Vaccines. Disclosures: Amy Lwin, RN, BSN, Janssen Pharmaceutical Company of J&J (Employee) Jerald Sadoff, MD, Janssen Pharmaceutical Company of J&J (Employee)